Proposition and Test of an Explanatory Model of Innovation Perception and It´s Consequences - Pereira, Murilo Junio Rezende (2019)
Objective: To propose and test a theoretical model to measure the innovation perception and the intention to renew the consumers annuity of its members. Method: A survey was carried out with fans of soccer clubs from all over Brazil and a sample of 883 elements was obtained. Data were analyzed using multivariate statistical techniques and structural equations modeling, attempting to validate the proposed model at the level of the scales used and the nomological chain. Originality/Relevance: Model development for an innovation perception by consumers measurement, as well as the verification and test. This study provide club managers with information on the variables that impact the perception and behavior of the fans will lead to the clubs better strategic planning in the quest to make the club a profitable organization. Results: Tested model has shown that the benefits provided by the Fan Loyalty Program generate a innovation perception triggering the perception of this products values. Perceived innovation and value positively impact the member's satisfaction, which leads them to renew the program annuity. Theoretical/Methodological Contributions: the innovations incorporated in the sporting sector are new actions that have the need for a models establishment that can support the managers decision process. Researchers should establish a continuing effort to comprehend how the perception of innovative products impacts consumers, which is important to assess the innovative products diffusion, not only by their past behavior, but also by future behavior intention, one of the present study objects.